Determinants Of Online Repurchase Intention On Indonesia - Kurniawan, Raymond; Wahyuningjati, Tri; Zein Saleh, Mohamad (Shofanah Media Berkah, 2023)
The rapid development of e-commerce in Indonesia makes the competition in this business increasingly fierce. This study aim to examines whetever E-satisfaction, Adjusted Expectation and Trust influence Repurchase Intention on Indonesia. By conducting an initial study of factors that can influence the repurchase intention and this can be used as a strategy. Through qualitative research where information is collected from several reliable source, The result of the study found that E-Satisfaction, Adjusted Expectation, and Trust have a direct positive effect on repruchase Intention. Happy and satisfied customer have a higher chance to do next order, while dissatisfied customer might have low even none motivation to do repurchase. Adjusted expectation act as post-hoc expectation that customer expect in service/product, that continuously learning as the market keep changing. Meanwhile trust is important key to maintain relationship with retaining customer and the very first purchase in e-commerce. In short, it can be said that the e-satisfaction, adjusted expectation, and trust play an important role in customer repurchase intention. Therefore, companies must provide a great and dynamic standard of product/service to gain customer trust, meet customer adjusted expectation and satisfied the customer. In this way, customer have higher chance to retain and increase customer’s repurchase intention.